Representation of Self-Concept in the Collection of Children's Stories from Bobo Magazine - Wita Siti Mahmudah; Seni Apriliya; Ahmad Mulyadiprana (OKARA: Jurnal Bahasa dan Sastra, 2021)
As construction of thought, self-concept will continue to grow and develop following the life experiences, one of which can come from stories. Therefore, this study aims to uncover and describe indicators of self-concept from children's stories. The data was obtained based on ten children's stories from the online version of Bobo magazine published in 2019-2020. This research used the content analysis method with categorization and tabulation until inference was found. The results revealed that Bobo magazine had implied self-concepts in the published stories. Among them, such as self-identity related to the labels attached by other characters as well as the character's desire to be what kind of self; personal behavior related to the views of other characters and figures in viewing their behavior; and self-judgment related to the acceptance or rejection of the character's behavior. Then, the physical self-concept associated with gender and character skills; moral self-concept related to the character's ability to control his behavior; personal self-concept related to good relations between characters; family self-concept related to the character's relationship with his family members; and social self-concept related to the character's relationship with his peers. These findings appear to confirm the representation of self-concepts in Indonesian children's short stories.